Persepsi Kemudahan dan Kegunaan Penggunaan Mobile Banking, Studi Mahasiswa di Manokwari - Yammes Jonas Batkunde; Joice Pangalimang; Irmawati Leppang (Journal of Innovative and Creativity, 2025)
The purpose of the study was to determine the simultaneous and partial influence of the variables of perceived ease and perceived usefulness on the variable of interest in using livin Bank Mandiri mobile banking on STIMIK Kreatindo Manokwari students. The analysis technique used was quantitative, with a sample size of 96 respondents, with the data analysis technique used in multiple linear regression. And the results of the study for the first hypothesis (H1) because t count 3.587> t table 1.98580 then there is an influence of perceived ease (X1) on Y (interest in using mobile banking) and a significance of 0.001 <0.05 then the first hypothesis (H1) is accepted. And for the second hypothesis (H2) because t count 6.261> t table 1.98580 then there is an influence of perceived usefulness on interest in using mobile banking and a significance of 0.000 <0.05 then the hypothesis (H2) is accepted. the results of the F test can be seen that the F-count 449.561 > F table 3.09 then there is an influence of perceived ease (X1) and perceived ease (X2) simultaneously together on Y (interest in using) then the third hypothesis (H3) is accepted.